PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF BERBASIS GAME VISUAL NOVEL PADA MATA PELAJARAN PENDIDIKAN PANCASILA DI SMA NEGERI 20 SURABAYA - Syach, Dhinendra Choirum Min Alfi; Listyaningsih, Listyaningsih (Universitas Negeri Surabaya (Unesa), 2023)
The current learning system necessitates instructional media that can meet the needs of learners. The existence of technology facilitates teachers in designing and creating instructional media that is most suitable for students, one of which is the use of games. This Research and Development (R&D) study aims to develop a game-based instructional media with a Visual Novel genre, expected to facilitate students in comprehending the material, particularly in the Senior High School Phase F, which is the Implementation of Pancasila in Daily Life. Additionally, the study seeks to assess the feasibility and the response of students towards the developed instructional media. The development process is carried out using the ADDIE model (Analyze, Design, Develop, Implementation, Evaluation), grounded in the cone of experience theory by Edgar Dale. Validation is conducted by media and subject matter experts, and for limited trial subjects, students from the 11th grade of SMAN 20 Surabaya are selected due to their high interest in learning with technology, as observed during the PLP implementation. Based on the validation results, the developed instructional media received an average score of 4.1 in the highly feasible category for media and 4.3 for the subject matter. The limited trial conducted by 30 students from the 11th grade yielded a score of 4. The results of the conducted tests lead to the conclusion that the Visual Novel game-based instructional media being developed is deemed suitable for use in the subject of Pancasila Education.